Elektroencefalografska koherenca med vidnimi in motoričnimi področji možganske skorje pri vidno-motorični nalogi - Brežan, Simon (Medicinski razgledi, 2005)
Background. The functional integration ( binding ) of different brain areas, for example as a possible mechanism for stimulus perception, may be mediated by the synchronizing oscillatory activity of neuronal populations, which can be determined by electroencephalographic coherence analysis. Visuomotor integration in a visuomotor task requires functional cooperation between the motor and visual cortical areas. Unilateral limb movements are based on the activation of contralateral primary motor cortex and bilateral activation of premotor cortices. Aim. Our main aim was to introduce a new method of coherence analysis and to compare our results obtained using an established model of the visuomotor task with other comparable studies, thereby assessing the validity of this method. The changes in coherence and power spectra of theleft and right hemispheres of the brain were then compared while the subjects performed the visuomotor task with the right or with the left hand. Hypothesis. It was assumed that the coherence between the visual and motor areas of the cortex would increase for the visuomotor task compared to the control tasks. It was also hypothesized that an increase in coherence and a decrease in the power spectrum while performing the task with the right hand would be greater in the left hemisphere and vice versa. Methods. 6 healthy, right-handed subjects were tested and their electroencephalograms were recorded while they performed 4 different tasks: a visuomotor task with the right and the left hand (which required good coordination between visual and motor brain areas), a visual task, a motor task and a visual and motor task (which required independent activation of the visual and motor areas). For coherence and spectral analysis, a special computer program was designed usingMatlab software. (Abstract truncated at 2000 characters).
Keywords: Electroencephalography; Elektroencefalografija; Cortical Synchronization; Kortikalna sinhronizacija; Motorična skorja; Visual Cortex; Vidna skorja; Motor Cortex; Adult; Alfa ritem; Alpha Rhythm; Beta ritem; Beta Rhythm; Odrasli; možgani; fiziologija; možganska skorja